The great deluge algorithm method to solve ITC 2007 examination timetabling problem - Poh, Yi Keng (2014)
There are several problems in the examination timetabling (exam-timeslot-room assignment) that involves assigning exams to a specific or number of timeslots and rooms, with the aim of fulfill the soft and hard constraints as much as possible. In the scientific literature, there are many techniques that have been used to solve the simplified examination benchmark datasets. The examination track of-the second International Timetabling Competition (ITC 2007) dataset is used for this research and this dataset had several novel constraints and also to those commonly used in the literature. The International Timetabling Competition (ITC 2007) have total of twelve dataset and each of them have different features. For example, number of exam, number of room and also number of timeslot. Great deluge algorithm is being used to solve the problem of timetabling.